Methods of financing of projects and oil and gas projects of common priority (A Case Study of Pars Oil & Gas Company) and comparison with Qatar and provide the optimal solution - Azarkish, l.; Varnamkhasti, T.Khalili (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
In this research, we consider the financial procedure of projects plan in the field of oil & gas to make a Comparison between Qatar & Iran, regarding the amount of investment & gas and oil production in the south pars common field. Accordingly, we're going to provide optimal solution to promote financing of projects & performance& plans in the area of oil & gas in the POGC. Through library studies, we gathered information regarding the amount of investment & removal in the common field in which two countries (Iran & Qatar) have down in the south pars. Also, by using of research literature which has been written of updated financing procedure, we have provided a questionnaire in which the validity of it has been examined by CRONBACH's alpha. Regarding subject of research, we select a statistic society from senior managers, intermediate managers, operations, head of department and senior experts and experts (knowledge contracts and financing of oil and gas projects) of national Iranian oil company (NIOC) & PARS oil & gas company (POGC) .the results acquired through library studies show that the amount of investment by Iran is 971197 USD billion & Qatar is 117191 USD billion; there for, the amount of removal gas by Iran is 759 million cubic meters & Qatar is 579 million cubic meters per day . Accordingly Qatar oil production is 7110111 Barrel per day but The Iranian oil layers still not reached the production stage. The analysis of the responses received, it is clearly show that PSA (production sharing agreement) is a suitable procedure to expedite increasing of removal / production in common fields.